Current Status of Semiotic Use - Sotanasathien, Surapongse (International Journal of Psychosocial Rehabilitation, 2020)
The state of sign and language is unstable. If it can be fluid that flows freely without intermittentbarriers. The change in disruptive innovation is a key factor in making the fluid sign/language no longer be static or frozen. The more we enter the digital age, the more the semiotics/language become more fluid so that we cannot separate truth from falsehood, accuracy leaves things wrong, real things out of illusions, freedom out of fuddle. And until he no longer knew his identity, because he was also trapped in the noose of illusion, for example, it reflects the sign, especially the language, as a fluid. It will have a more fluid state during the disruptive innovation era. As a result, the Langue is blended with Parole, especially in social media. It comes to the point that they cannot be separated as they are the languages of society. The disruptive innovation causes digital concepts to replace the analog ones, which makes that dualism approach of the sign. There is nothing between the with and the without of software development processing. Nevertheless, its application continues with a more realistic world flowing digital literacy also makes signs, languages, and codes become fluid.